GE_GERICHTE P/15825/2019 vom 7. Oktober 2020 - GE Cour de justice (2020)
DÉLAI DE RECOURS;OPPOSITION(PROCÉDURE);ORDONNANCE PÉNALE;DÉFAUT(CONTUMACE);RESTITUTION DU DÉLAI;COMPÉTENCE;DÉCISION D'IRRECEVABILITÉ | CPP.90; CPP.91; CPP.356.al4; CPP.93; CPP.94